Entrance test scores and grade six average grades as predictors of performance in high school science and mathematics - Cervera, Oliva M. (1977)
The objectives of the study was to find out the relationship of the entrance test scores and the grade six average grades to the academic achievement in mathematics and science of the students of Quezon City Science High School, and to determine the extent to which these two can predict performance in the two subject areas. The study showed that grade six average grade is highly correlated with the average grade in science and mathematics and hence it is a good predictor of performance in these areas. The entrance test scores have a low correlation with average grade in science and mathematics, hence they are not good predictors of performance.
"March 1977."
Thesis (M.A.T. Physics)--University of the Philippines, Diliman.
Keywords: Mathematical ability -- Testing; Academic achievement -- Philippines -- Quezon City